Winter Habitat Use by American Marten, Martes americana, in Western Alberta Boreal Forests - Proulx, Gilbert (The Canadian Field-Naturalist, 2006)
Although the American Marten (Martes americana) is found in most forest regions of Alberta, little is known about its choice of winter habitats. This study investigated winter habitat use by American Marten in Weyerhaeuser’s Grande Prairie Forest Management Area (FMA) using snowtracking along 128.2 km of seismic lines inventoried in winters 1999, 2002, and 2005 with snowmobiles. American Marten tracks (n = 44) occurred significantly less frequently than expected (P < 0.001) in immature/young pole stands, but more frequently than expected (P < 0.02) in mature/old growth mixedwood stands. American Martens apparently used young forests, and mature/old coniferous and deciduous stands, according to their availability. Forest development plans should be developed locally to retain late successional forests that meet the winter habitat requirements of American Marten.